Statistical yearbook = Annuaire statistique - Unesco (Paris : UNESCO Pub., 1999)
'Reference tables, education, science and technology, and culture and communication.'
PTSL:- yearbook :1994,1999
Keywords: Intellectual life -- Statistics -- Periodicals; Literacy -- Statistics -- Periodicals